(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
This article analyzes the role of the Soviet era in the civilization of Central Asia based on historical sources and scientific research. It extensively covers the socio-political life of the peoples of Central Asia during the Soviet period, economic development, changes in cultural and scientific processes, as well as issues of national identity. While the Soviet era created certain opportunities for modernization, industrialization, education and scientific development in the development of the peoples of Central Asia, on the one hand, the restriction of national and religious values, the policy of Russification and the negative consequences of centralized management were observed